2011
DOI: 10.1097/olq.0b013e31822545c0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Polyclonal ELISA HPV Serology Assay as a Biomarker for Human Papillomavirus Exposure

Abstract: Background Seropositivity to HPV16 and 18 antibodies is used as a measure of cumulative HPV exposure and as a stratifier of HPV exposure for vaccine efficacy analyses. Overall performance of these assays, as a measure of HPV exposure, has not been evaluated. Methods Using data from the enrollment phase of the HPV16/18 vaccine trial in Costa Rica, we evaluated the performance of the polyclonal ELISA HPV16 and 18 serological assays as a measure of HPV exposure. Biological (for eg. HPV infection at the cervix) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…This is consistent with documented associations between GST-L1 seropositivity and ever/never sexual activity, age at sexual debut, and lifetime number of sexual partners [22,31,40]. VLP-ELISA is an established HPV exposure marker [11], and we observed moderate concordance between GST-L1 and VLP-ELISA. A previous study compared GST-L1 to a VLP multiplex immunoassay, which is biologically similar but technically different from our VLP-ELISA.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with documented associations between GST-L1 seropositivity and ever/never sexual activity, age at sexual debut, and lifetime number of sexual partners [22,31,40]. VLP-ELISA is an established HPV exposure marker [11], and we observed moderate concordance between GST-L1 and VLP-ELISA. A previous study compared GST-L1 to a VLP multiplex immunoassay, which is biologically similar but technically different from our VLP-ELISA.…”
Section: Discussionsupporting
confidence: 92%
“…ELISA positivity was 3-fold higher than cLIA positivity suggesting that the observed differences in vaccine efficacies among the subset of HPV na€ vepopulations may be due, in part, to the inconsistent cutoffs in the assays used to define the HPV-na€ ve populations. The fact that cLIA did not classify as many seropositives as the ELISA suggests that the cutoff used in the cLIA assay is higher (thus not sensitive) for detecting exposure; in contrast, previous published work suggests that ELISA assays are a good measure of HPV exposure (20)(21)(22).…”
Section: Discussionmentioning
confidence: 49%
“…While this resulted in an efficient sampling, a limitation was that the samples selected were on the basis of seropositivity by ELISA. We believe this does not bias our study, as it measures a broader range of antibodies, and we previously showed this ELISA assay to be a good biomarker of exposure at the suggested cutoff (20,21). ELISA and cLIA are different from each other based on the laboratory-determined cutoff.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of antibodies has been used as an epidemiological measure of HPV exposure and as a marker of immunity or protection from subsequent infections to inform vaccine policy. 13,14 Serological studies suggest that approximately 20% to 50% of women with active cervical HPV infection do not have detectable type-specific anti-HPV antibodies, 15,16 and that it can take more than a year after the initial infection to develop antibodies 17 but, once present, has been shown to persist for many years. 18,19 Studies using detection of antibodies to HPV have mostly been performed on plasma or serum samples, but Waterboer and colleagues 20 recently demonstrated the successful use of dried blood spots (DBS) for detection of antibodies to HPV.…”
mentioning
confidence: 99%